Pengaruh Kompensasi, Motivasi Kerja dan Pengalaman Kerja Terhadap Produktivitas Kerja Karyawan Pada CV. Sugeng Mulya - Pramono, Bagus Dwi; , Drs. Ma'ruf, M.M (2015)
The aim in this study is to analyze: Analyze the effect of compensation on employee productivity, Analyze the effect of work motivation on employee productivity, Analyze the effect of work experience on employee productivity, Analyze the effect of compensation, motivation and work experience on employee productivity in CV. Sugeng Mulya. This research is a survey. The population is all employees CV. Sugeng Mulya, amounting to 176 people. A sample of 100 respondents using Slovin formula. The method of data analysis using : test research instruments, namely the validity and reliability, the classic assumption test, namely normality test, multicollinearity, heteroscedasticity, test hypotheses, namely linear regression test multiple, t test, F test and test determinacy. The results showed that: (1) Testing multiple linear regression showed compensation (X1) has the greatest regression coefficient so that compensation is the most dominant variable affecting employee productivity in the CV. Sugeng Mulya. (2) t test result that compensation, motivation and work experience are individually significant effect on employee productivity in the CV. Sugeng Mulya. (3) F test result that compensation, motivation and experience working together have a significant effect on employee productivity in the CV. Sugeng Mulya.